Research in the social scientific study of religion - Village, Andrew; Hood, Ralph W. Jr. 1942- (Brill, 2016)
This volume includes a wide range of papers that explore individual and institutional aspects of religion from a social-science perspective. The special section has articles related to the practice of prayer, and includes studies from the USA, Europe, and the Middle East. The general papers include studies on coping strategies, God representations, spirituality versus religion, self-control in a Muslim context, and faith-based organizations in Cambodia. Together these papers form a valuable collection indicating the depth and vibrancy of research in these fields
Einzelaufnahme eines Zeitschriftenbandes
Keywords: Religionssoziologie; Aufsatzsammlung